Epiploic Appendagitis and Omental Infarction as Rare Causes of Acute Abdominal Pain in Children - Federica Bianchi; Carlos Leganés Villanueva; Núria Brun Lozano; Ilaria Goruppi; Susana Boronat Guerrero (Pediatric Reports, 2021)
Omental infarction and epiploic appendagitis are rare causes of acute abdominal pain in the pediatric population. Radiological evaluation is necessary to establish a specific diagnosis and to differentiate appendicitis from these conditions as they can be often managed conservatively without surgical intervention.